Impact of E- Learning Management System Adoption at Mbarara University of Science and Technology - Kabarungi, Moreen; Musiimenta, Angella; Atuhe, Aarone (International Journal of Computer Trends and Technology (IJCTT), 2016)
The wider adoption of Information Communication Technologies (ICTs) has provided opportunities to utilize electronic teaching and learning environments (e-learning) such as Learning Management System (LMS) in Higher Institutions of learning. However, evaluating LMSs especially in developing countries has largely been focusing on acceptance issues, while giving less attention on impact evaluation. This study qualitatively assessed the impact of using LMS on teaching and learning based on interviews with ten (10) students and en (10) lecturers of Mbarara University of Science and Technology (MUST). In May 2016, participants took part in individual interviews that mainly focused on their experiences and benefits of using LMS at MUST. The digitally recorded interviews were transcribed, and analyzed using thematic analysis. Reported impacts of LMS include: 1). improved engagement and interactions using discussion boards and chatting forums as LMS tools; 2). Offering unlimited accessibility of teaching and learning materials; 3) being cost-effective; and 4) improved management of teaching and learning resources. Overall LMS is useful for offering enriched teaching and learning experiences.
Keywords: Information Communication Technologies (ICTs); Electronic Learning (e-Learning); Learning Management Systems (LMS)